Cd-CeO2@C: Synthesis via consumption of Cd2+ and organic pollutants and removal of organic pollutants - Heyun Tan; Yuantao Cai; Gangfeng Liang; Paolo Aprea; Shiyou Hao (Arabian Journal of Chemistry, 2024)
In this study, a Cd-CeO2@C photocatalyst was produced via the calcination of a precursor (Cd-Ce(OH)4@AR14) obtained by co-precipitation of Ce(NO3)3·6H2O, Cd(NO3)2·4H2O and acid red 14 (AR14). The structure, composition, morphology, and optical properties of the synthesized products were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), infrared spectrum (FT-IR), Ultraviolet–Visible Diffuse Reflectance Spectroscopy (UV–Vis DRS), X-ray photoelectron spectroscopy (XPS) and Photoluminescence Spectroscopy (PL). The photocatalytic activity of the synthetized materials was evaluated by performing the degradation of AR14. The results showed that the band gap of CeO2 could be effectively reduced by Cd-doping, and that carbon bonds could decrease the recombination rate of photogenerated electrons and holes, resulting in enhancing the photocatalytic efficiency of the synthesized materials compared with that of pure CeO2. Hydroxyl groups play an important role in the photocatalysis because the adsorption of AR14 over Cd-CeO2@C is greatly affected by the content of hydroxyl groups. Moreover, effect of oxygen vacancies on the photocatalytic efficiency was investigated and the results showed that oxygen vacancies could improve the photocatalytic efficiency of the resulted samples.